EVALUATION OF THE PAVEMENT ROUGHNESS OF AMIR TEMUR STREET IN TASHKENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article presents the development of recommendations based on the results of an assessment of the transport and operational condition of city streets.